Parateksty w polskich przekładach powieści Miloša Crnjanskiego - Filipek, Małgorzata (Przekłady Literatur Słowiańskich, 2017)
Paratexts in Polish Translations of Miloš Crnjanski’s Literary Works The article discusses paratexts in Polish translations of M. Crnjanski’s poetry and prose. The corpus of the article includes the Polish translations, which were published in six volumes. Various types of paratexts of the translations have been analyzed here: the translator’s paratexts and the editor’s paratexts, verbal and non-verbal paratexts, introductions and notes included in the Polish versions of M. Crnjanski’s works. The authors of the Polish paratexts — Danuta Cirlić-Straszyńska, Branislav Ćirlić, and Grzegorz Łatuszyński are also translators of Crnjanski’s works from Serbian into Polish. Keywords: literary work, translation, verbal and non-verbal paratexts